Flexible Strain Sensor Based on Metallized Polyurethane Conductive Sponge Using Laser Direct Writing Process - Dong, Liang; Li, Chen; Han, Peiying; Song, Longgang; Chen, Yangyang (Manufacturing Technology Journal, 2024)
Flexible strain sensors show great potential in the field of wearables and health monitoring. However, the application of traditional strain sensors on flexible substrates is still limited, and the development of sensors with high sensitivity, excellent stability and good durability is a current research focus. Aiming at the limitation of traditional strain sensor in flexible materials, a flexible strain sensor based on Kirigami structure is proposed. In this study, a Metallized Polyurethane Conductive Sponge (MPCS) was used as the sensor substrate. In the preparation process, we used laser direct writing process to achieve the preparation of highly accurate, patterned sensitive structures. In addition, the length parameter of rectangular hollow structure is optimized by finite element analysis to improve the stability of the sensor. The experimental data show that the prepared flexible strain sensor has a high strain range (130%), a maximum sensitivity of (GF=1.184), a response/recovery time of 168/186 ms, a good linearity, and a very good repeatability and stability during 2000 working cycles.The preparation method provides an effective means for realizing high-performance flexible thin film sensors, and has broad application prospects in intelligent wearable devices, human-computer interaction, health monitoring and other fields.
Keywords: Polyurethane; Porous material; Flexible sensor; Laser direct writing technology; Kirigami structure